Impacts of two types of El-Niño on the winter North Pacific storm track - Minghao Yang; Chongyin Li; Yanke Tan; Xin Li; Xiong Chen (Environmental Research Letters, 2020)
In the present study, the impacts of eastern Pacific (EP) and central Pacific El-Niño on the winter North Pacific storm track (WNPST) are investigated, and the possible reasons for the different responses of the WNPST to the two types of El-Niño are revealed. It is found that only EP El-Niño episodes have a distinct influence on the strength and movement of the WNPST. During EP El-Niño episodes, the WNPST is significantly enhanced and extended equatorward. The patterns of atmospheric baroclinicity anomalies are consistent during the two types of El-Niño. The enhancement and equatorward extension of the WNPST during EP El-Niño episodes can be attributed to anomalous baroclinic energy conversion. In addition, EP El-Niño episodes can also intensify the strength of the WNPST by warming the lower-tropospheric air upstream of the WNPST, which generates more synoptic-scale disturbances entering the WNPST.